Regulatory T Cell and T Helper 17 Cell Imbalance in Patients with Unexplained Infertility - Lu L; Lu Y; Zhang L (Dove Medical Press, 2024)
Liang Lu,1,* Yan Lu,2,* Longyi Zhang2 1Department of Reproductive Center, Affiliated Dongyang Hospital of Wenzhou Medical University, Dongyang, Zhejiang, People's Republic of China; 2Clinical Laboratory, Affiliated Dongyang Hospital of Wenzhou Medical University, Dongyang, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Longyi Zhang, Clinical Laboratory, Affiliated Dongyang Hospital of Wenzhou Medical University, Dongyang, Zhejiang, People's Republic of China, Tel +86 15267914600, Email happy_zhang1y@163.comPurpose: Female infertility is a global health concern. The aim of this study was to investigate the relationship between regulatory T (Treg) cells and helper T cells 17 (Th17) in peripheral blood and unexplained infertility (UI). In addition, we explored potential valuable diagnostic biomarkers for patients with UI and ascertained whether Treg and Th17 cells are associated with primary and secondary UI.Patients and Methods: The patients underwent standard fertility evaluation test, including blood tests, ultrasound examination, fallopian tube tests, ovulation assessment, and male partner's semen analysis. According to the inclusion and exclusion criteria, this study enrolled 37 patients with UI (30 with primary UI and 7 with secondary UI) and 26 age-matched healthy volunteers as the control group. Flow cytometry was used to detect the frequency of Treg and Th17 cells. The area under the receiver operating characteristic curve (AUC) with a 95% confidence interval (CI) was used to assess the diagnostic performance. An AUC > 0.800 indicated good diagnostic performance.Results: The percentage of Treg decreased significantly, whereas the percentage and absolute count of Th17 cells increased. Moreover, the Th17/Treg ratio in patients with UI increased significantly. As a diagnostic biomarker for UI, the Th17/Treg ratio exhibited remarkable diagnostic performance (AUC: 0.813 (95% CI = 0.709- 0.917)). However, the percentages and absolute counts of Treg and Th17 cells in the peripheral blood of women with primary and secondary UI, as well as their Th17/Treg ratios, did not differ significantly.Conclusion: The distribution of Treg and Th17 cells is imbalanced in patients with UI. Therefore, the Th17/Treg ratio may be a promising indicator of UI. However, there were no significant differences in the distribution of Treg and Th17 cells between women with primary and secondary UI.Keywords: female infertility, regulatory T cell, T helper 17 cell, unexplained infertility, immunology, biomarkers